2008
DOI: 10.1002/mnfr.200700369
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of selenium chemoprevention and therapy in prostate cancer

Abstract: Public reporting burden for this collection of information is estirmated to average 1 hour per response, including the time for reviewing instructions, searching exlisng data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comrments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Washington Headquarters Services, Directorate for Information Operations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 108 publications
1
20
0
Order By: Relevance
“…Although preclinical and early clinical studies suggested that selenium supplementation could prevent prostate cancer (2), results from a recent large randomized trial failed to show a significant effect of organic selenium alone or in combination with other agents on the incidence of prostate cancer (3). Meanwhile, little is known regarding the use of inorganic selenium as an anticancer agent.…”
Section: Introductionmentioning
confidence: 99%
“…Although preclinical and early clinical studies suggested that selenium supplementation could prevent prostate cancer (2), results from a recent large randomized trial failed to show a significant effect of organic selenium alone or in combination with other agents on the incidence of prostate cancer (3). Meanwhile, little is known regarding the use of inorganic selenium as an anticancer agent.…”
Section: Introductionmentioning
confidence: 99%
“…It is specifically incorporated as the amino acid selenocysteine into 25 so-called selenoproteins, many of which catalyze redox reactions with Se at the active site (1)(2)(3). Increased intake of Se has been suggested to have anticarcinogenic effects, and numerous mechanisms have been proposed to explain this property: reduction of DNA damage, oxidative stress, or inflammation; also, induction of phase II enzymes, enhancement of immune response, inhibition of cell cycle and angiogenesis, and induction of apoptosis were proposed (4). Intervention studies in humans have shown that supplementation of Se leads to an increase in concentration and/or activity of circulating selenoproteins, such as selenoprotein P (SePP) or glutathione peroxidases (GPx; refs.…”
Section: Introductionmentioning
confidence: 99%
“…14 Moreover, studies evaluating the importance of selenium in cancer treatment in humans refer more to the role of this mineral in prostate and colorectal cancer [63][64][65][66][67][68][69] and less to its role in cases of bladder cancer. 70,71 conclusion Low selenium concentrations, as well as a reduced expression of selenoproteins, are associated with a high risk of cancer.…”
Section: Selenium Supplementation As a Chemopreventive Agentmentioning
confidence: 99%